"Promote locally led initiatives to fight female genital mutilation/cutting (FGM/C)" lessons from anti-FGM/C advocates in rural Kenya - Purity Mwendwa; Naomi Mutea; Mary Joy Kaimuri; Aoife De Brún; Thilo Kroll (BMC, 2020)
Abstract Background Female Genital Mutilation/cutting (FGM/C) is a tradition rooted in culture and involves the partial or total removal or other injury to the female genital organs for non-medical reasons. In Kenya, initiatives to abandon the practice have included 'alternative' ritualistic programmes (ARPs) combined with intensive community sensitisation about FGM/C to achieve attitudinal and behavioural changes. While there are indications of the effectiveness of these interventions, FGM/C continues to be practiced within certain groups in Kenya. This study explored the views of anti-FGM/C advocates on the barriers and facilitators to tackling FGM/C within the Meru community in Kenya. Methods Data were obtained using 4 Focus Groups (FGs) with 30 anti-FGM/C advocates from Tigania East and West in Meru county. Thematic framework analysis guided the analysis based on four main questions: 1) How has the cultural meaning of FGM/C evolved over time? 2) What are the perceptions in relation to the effectiveness of anti-FGM/C interventions? 3) How effective are interventions and campaigns to end FGM/C in Meru county? 4) What actions are perceived as the most likely to bring about change? Results There has been a substantial shift in the culture of FGM/C and the number of families carrying out the practice in Meru county has decreased in recent years. Participants noted five actions likely to bring about change; 1) reviving and supporting ARPs, 2) encouraging fathers' involvement in the upbringing of their daughters,3) inclusion of the topic of FGM/C in the current education curriculum and public fora, 4) strengthening the community policing strategy -Nyumba Kumi, 5) and setting up community centers for orphans. Conclusion Our findings demonstrate the significance of locally led initiatives to fight FGM/C. It also became clear that change would have to start at the family level with parents, particularly fathers, taking on a more active role in the lives of their daughters. Providing education about FGM/C to communities, particularly young men coupled with keeping girls in school appeared to be some of the most effective ways of fighting FGM/C. At the community level, the church became particularly crucial in challenging the practice of FGM/C.